Pengaruh Pendidikan Kesehatan Menggunakan Media Leaflet Terhadap Pengetahuan Ibu Hamil Tentang Pemeriksaan Jantung Bawaan - Suryani, Emy; Aji Pamungkas, Atik Mahmudah; Ayuningtyas, Asri Milasari (JURNAL KESEHATAN TERAPAN, 2025)
ABSTRAK Congenital Heart Disease (CHD) is one of the congenital abnormalities in newborns (BBL) that contributes to infant and child morbidity and mortality worldwide. Congenital heart disease (CHD) is the most common type of congenital abnormality found in newborns (Ministry of Health, 2023). The incidence of CHD is 9.1 per 1000 live births and is commonly found in Asia, Europe, and North America (Gumilar and Pradnyani, 2020). Based on the 2022 Indonesian Health Profile, deaths in the neonatal period aged 0-28 days were recorded at 18,281 deaths, 5% of deaths were caused by congenital abnormalities (Ministry of Health, 2022). Early CHD screening needs to be known by mothers, so that mothers understand the importance of having their children examined by health workers. Efforts so that mothers understand about early CHD screening, it is necessary to increase mothers' knowledge about CHD. Based on the results of interviews with pregnant women in January 2024, it was stated that at PMB Haryanti there had never been any health education about PJB screening and there was no communication media explaining PJB screening. The purpose of this study was to determine the effect of health education using leaflet media on mothers' knowledge about PJB at PMB Haryanti Wonogiri. This study used a quantitative one group pretest and posttest design. The population in this study were pregnant women in the PMB Haryanti Wonogiri work area and the sample used was 28 people. The analysis test used the T test with a significance value of 0.000, this value is smaller than 0.05 so that there is an effect of health education using leaflets on pregnant women's knowledge about Congenital Heart Disease screening.